Bibliometric Analysis of Inclusive Tourism Communication Research in Indonesia 2014-2024 in an Effort to Explore Opportunities and Determine Development Directions - Ramadhanty, Ghina; Novianti, Evi; Khadijah, Ute Lies Siti (Journal La Sociale, 2025)
This study aims to analyze the development of research on inclusive tourism communication in Indonesia over the past decade (2014–2024) using a bibliometric approach. Data were obtained from the Scopus database using the keywords "tourism," "inclusive," "accessibility," "special needs," "disability," and "Indonesia." Visualization results using VOSviewer show an increasing publication trend since 2018, dominated by keywords such as tourism, Indonesia, accessibility, and disability, indicating a research focus on accessibility and social justice issues in the tourism sector. Publications are dominated by scientific articles and conference proceedings, while institutional contributions are still concentrated in several major universities in Indonesia. This analysis reveals the potential for strengthening cross-institutional and cross-disciplinary collaboration to support the development of more inclusive and sustainable tourism in the future.